Anisotropy characterization of upper shanghai clays: Shear strength and small-strain stiffness - Lixin Lan; Wenxuan Zhu; Guanlin Ye; Qi Zhang; Tongshuai Yang (Journal of Rock Mechanics and Geotechnical Engineering)
Comprehensive investigations have been conducted to study the structure and overconsolidation of upper Shanghai clays, i.e. Layers 2–6 clays, typically located at depths of 30–40 m. However, limited information is available on their anisotropy, and even less is known about the correlation between structure, overconsolidation, and anisotropy. In this study, the undrained anisotropy characteristics of shear strength and small-strain shear stiffness in upper Shanghai Layers 2–6 clays were thoroughly assessed using a series of K0-consolidated undrained triaxial compression (TC) and triaxial extension (TE) tests (K0 is the coefficient of lateral earth pressure at rest). The effective stress paths, shear strength, and small-strain shear stiffness from the undrained TC and TE tests demonstrate the anisotropic behaviors in upper Shanghai clays. Analyses of data from upper Shanghai clays and other clays worldwide indicate that the shear strength anisotropy ratio (Ks) converges at 0.8 as the overconsolidation ratio (OCR) and plasticity index (Ip) increase, while the small-strain shear stiffness anisotropy ratio (Re) converges at 1.0. The influence of OCR on Ks and Re is more pronounced than that of Ip and sensitivity (St). Nevertheless, no clear correlation between Ks and Re is observed in upper Shanghai clays.